The influence of polymer on rheological and thermo oxidative aging properties of modified bitumen binders - Bala, N. (Penerbit UTM Press, 2017)
Polymer modified bitumen (PMB) has been used for many years to improve the performance of asphalt concretes against premature pavement defects. In this research, modified samples were prepared with 2, 3, 4, 5 and 6 Linear Low Density Polyethylene (LLDPE) polymer by weight of bitumen binder. The influence of LLDPE polymer was evaluated through binder properties test which includes penetration, softening point, storage stability, temperature susceptibility, rutting, fatigue and thermal oxidative aging resistance from a dynamic shear rheometer (DSR) measurements at a temperature of 20OC to 60OC. Results show that LLDPE polymer has a significant effect on binder properties. Penetration decreases and softening point increases with increasing LLDPE content on the modified binder after aging, which implies LLDPE improves the thermo oxidative aging resistance of the binder. Furthermore, the storage stability test shows that at higher LLDPE concentrations phase separation may occur. DSR analysis shows that modified binders have lower temperature susceptibility and higher aging resistance with increased stiffness and elastic behavior compared with unmodified binders. In addition, modified binders show enhanced resistance against high temperature rutting and at low temperature fatigue performance. It was found that the optimum LLDPE content is 6. © 2017 Penerbit UTM Press. All rights reserved.